The Effectiveness of Binahong (Anredera cordifolia) Leaf Extract Ointment in Stimulating Collagen Regeneration in the Dorsal of Mice - Okven, Noura Ramadhani Putri; Alzena, Safa; Nadifah, Umi (Proceeding International Conference on Religion, Science and Education, 2026)
Improperly treated incision wounds have the potential to cause infection and slow down the healing process. One approach to accelerating tissue regeneration is the use of bioactive compounds found in medicinal plants. Binahong leaves (Anredera cordifolia) are known to contain flavonoid compounds that play an important role in increasing collagen fiber production, thereby greatly contributing to the wound healing process. This study aims to determine the effectiveness of binahong leaf extract ointment by comparing control variables and the treatment of binahong leaf extract ointment on collagen fiber density after wounding on the dorsal of the mice. This study uses a test-only control group experimental design with 16 mice divided into 4 groups, with each group consisting of 4 mice. Two groups were given binahong leaf extract ointment (P1, P2) for different durations, namely 3 days and 4 days, with an extract concentration of 15% along with two control groups for durations of 3 days and 5 days (P3, P4). Incision wound were made 1,2 cm long and 0,5 cm deep on the dorsal of the mice. They were then observed macroscopically (measuring wound size) and microscopically (assessing collagen fiber density through scoring by an anatomical pathology specialist). The results showed that the treatment groups given binahong leaf extract ointment experienced an increase in collagen fiber density with an average score of 3,375 and a reduction in wound size 0,1 x 0,06 cm. In contrast, the control groups only reached an average score of 2 with wound size reduced to 0,6 x 0,06 cm. These data indicate that binahong leaf extract ointment is effective in accelerating the healing process of incision wound through the mechanism of increasing collagen fiber density and reducing wound size.